Un-reading Patriarchal Interpretations of the Qur’an: Beyond the Binaries of Tradition and Modernity (American Journal of Islam and Society, 2007)
I would like to thank AMSS, and specially Jamin Zine, for inviting me toaddress your conference on “Islam: Tradition and Modernity” today. Since Iam in the midst of enjoying your splendid hospitality, I feel I should beginwith an apology for what I am about to say. A polite guest would havepraised the food and your conference and gone home without being criticalof anything. But unfortunately for you, I was born with an impolitic geneand so I am going to take this opportunity to critique the way in which yourconference is framed.The basic point I will make is a simple one: It is not very productive tostudy Islam through the lenses of tradition and modernity. This is not becauseone cannot say anything meaningful about Islam in those two contexts;rather, it is because binary modes of thinking are themselves problematic. Iwill make this point in two ways: first by critiquing the tradition vs. modernitybinary and binaries in general and, second, by sharing my own work onQur’anic hermeneutics as an example of how we might get beyond binaries.Whether my comments will serve to muddy the waters or to clarify themremains to be seen ...